2010
DOI: 10.5194/hess-14-2141-2010
|View full text |Cite
|
Sign up to set email alerts
|

Land surface temperature representativeness in a heterogeneous area through a distributed energy-water balance model and remote sensing data

Abstract: Abstract. Land surface temperature is the link between soilvegetation-atmosphere fluxes and soil water content through the energy water balance. This paper analyses the representativeness of land surface temperature (LST) for a distributed hydrological water balance model (FEST-EWB) using LST from AHS (airborne hyperspectral scanner), with a spatial resolution between 2-4 m, LST from MODIS, with a spatial resolution of 1000 m, and thermal infrared radiometric ground measurements that are compared with the repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…In that study, they found that the consideration of spatially averaged T s , besides streamflow, improved monthly evapotranspiration predictions by up to 20%. Similar efforts were undertaken by Corbari et al () and Silvestro et al ().…”
Section: Introductionmentioning
confidence: 61%
“…In that study, they found that the consideration of spatially averaged T s , besides streamflow, improved monthly evapotranspiration predictions by up to 20%. Similar efforts were undertaken by Corbari et al () and Silvestro et al ().…”
Section: Introductionmentioning
confidence: 61%
“…The FEST-EWB model is a distributed hydrological energy water balance model (Corbari et al 2010(Corbari et al , 2011(Corbari et al , 2013 and was developed starting from FEST-WB (Mancini 1990, Rabuffetti et al 2008.…”
Section: Fest-ewb Hydrological Modelmentioning
confidence: 99%
“…The FEST-EWB model was proved to make accurate predictions of actual evapotranspiration by comparisons against energy and mass exchange measurements acquired by an eddy covariance station (Corbari et al 2011), and also at the agricultural district scale by comparisons with ground and remote sensing information (Corbari et al 2010). …”
Section: Fest-ewb Hydrological Modelmentioning
confidence: 99%
“…It is simply a composite generated by averaging eight days of daily LST product (MOD11A1). The MODIS LST products are validated over a range of representative conditions with well-defined product uncertainties (Wan 2008), and they have been satisfactorily used in a wide variety of scientific studies (Hall et al 2008;Bookhagen and Burbank 2010;Neteler 2010;Corbari et al 2010;Gutmann and Small 2010). Tile h25v06 covers the entire study area and both MODIS datasets were downloaded from the WIST of NASA.…”
Section: B Model Evaluationmentioning
confidence: 99%